Gender and Racial Differentials in Promotions: Is There a Sticky Floor, a Mid-Level Bottleneck, or a Glass Ceiling? - Yap, Margaret; Konrad, Alison M. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2009)
SummaryUsing a proprietary dataset containing personnel records on over 22,000 full-time, non-unionized employees from a large Canadian firm with nationwide operations from 1996 to 2000, this paper explores the incidence of promotion for women and racial minorities. The findings show that women and racial minorities are less likely than their white male counterparts to be promoted. For both white women and minority women, the disadvantage is most severe at the lower rungs of the organizational hierarchy, lending support to the “sticky floor” hypothesis. Significant promotion disadvantages occur for white women, visible minority women, and visible minority men at the middle ranks of the organization, and visible minority men continue to experience a promotion disadvantage at the highest organizational levels.